Place-Name Loaning Patterns as Cultural Survival Strategies in Sami Contexts - Valtonen, Taarna (Journal of Northern Studies, 2018)
This paper discusses the place-name loaning patterns of one South Sami and one Inari Sami community that have plenty of parallel names in their area. The time span studied reaches from the end of the nineteenth century to the middle of the twentieth century. The loaning and borrowing processes are analyzed and interpreted in a thoroughly studied cultural context. The author claims that the differences in loaning reflects different strategies that aim to secure the existence of minority language and culture, and that the place-names have been used as means of manifesting one’s cultural ownership to the land. The most important results based on the quality and distribution of the parallel names in the South Sami area reflects the existence of two separate name systems and a protective purist strategy toward outsiders. In the Inari Sami area the results indicate that the local Sami community has an open and pedagogical strategy towards outsiders and because of this they have shared the language-cultural code to the Finns. The author has been inspired in her study by the ideas presented in the field of ecological linguistics and cultural onomastics. This paper is based on the results of the author’s doctoral dissertation.